Ségrégations et parcours professionnalisés des sortants du supérieur - Philippe Lemistre (Populations Vulnérables, 2018)
According to Pierre Merle, if young people of modest social origin raise their level of education, it is towards the sectors and specialties least likely to allow privileged access to the labor market. It is “segregative democratization”, which this article broadens to include higher education graduates by examining the segregative nature of educational pathways, whether or not they include professional graduates. The segregated democratization linked to the study path implies that the professional nature or not of the degrees of the study path, differentiates the population in terms of social origin and influences the success of the final diploma, the continuation of studies and access to the labor market. Indeed, the surveys conducted from the 2013 CEREQ survey highlight the segregation of vocational professionalized study pathways.